Sobre o Episódio do Mahabharata conhecido como Bhagavad-Gita, de Wilhelm Von Humboldt (Revista Eletrônica Estudos Hegelianos, 2023)
Published in 1827 as two articles, Hegel’s text is a direct answer to Humboldt’s articles on August Schlegel’s recent Bhagavad-Gita translation. It’s the author’s longest consideration on the subject.